Dhundhunan: Asimilasi Budaya dan Pergeseran Nilai - Agus Fakhrina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This research explores the assimilation of Islamic culture in Javanese culture in the dhundhunan ceremony that is performed in the Javanese Muslim community living in Karangjompo, Tirto, Pekalongan, Central Java, and the value changes in that ceremony. To achieve the aim of this research, observation and interviews were conducted. It was found that there were some assimilations and value changes in that ceremony, i.e., prayers performed in the ceremony adopted Islamic culture, such as asking God for safety by reciting shalawat barzanji. The meaning of the symbols of uborampe in that ceremony has been forgotten by the community. They perform the ceremony only formally without caring about the meaning or experiencing its sacred values.